Developing Science Process Skills and Problem Solving Abilities Based on Outdoor Learning in Junior High School (Jurnal Pendidikan IPA Indonesia, 2017)
This research aims to develop science process skills and problem-solving abilities based on outdoor learning in junior high school. This study uses a mixed method design embedded experimental models. Data was performed in the qualitative and quantitative analysis. Qualitative data analysis is used to determine the science process skills while quantitative data analysis is used to determine the increasing problem-solving ability by using normalized gain (N gain) formula. The results show that the science process skills developed at every phase comprise of making observations, formulating hypotheses, experiment, create data, classify and analyze the data, formulating its conclusions, communicate, and apply the concepts and make predictions obtained by the average value of 75.33 in the good category. While the problem-solving ability of students based on outdoor learning also increased by 0.58 in the medium category. The conclusions of this research show that the application of outdoor learning can be teacher use as an alternative to learning, so it is quite effective in developing science process skills and problem-solving abilities.